2006
DOI: 10.1007/s00535-005-1752-3
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation profile in gallbladder cancer

Abstract: The high frequency of gene methylation (with the exception of MLH1) and the high agreement between AIP and methylation of the gene promoter area for the MLH1, APC, and CDH1 genes suggest that the inactivation of tumor suppressor genes and of the genes related to the control of cellular proliferation through this mechanism is involved in gallbladder carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 31 publications
4
33
1
7
Order By: Relevance
“…This value is lower than those from two GC studies in the literature [34,35] . On the other hand, the FHIT hypermethylation frequency was 61.5% in nonneoplastic samples, which is higher than in other studies.…”
Section: Dna Hypermethylation In Gatric Tissuecontrasting
confidence: 60%
See 1 more Smart Citation
“…This value is lower than those from two GC studies in the literature [34,35] . On the other hand, the FHIT hypermethylation frequency was 61.5% in nonneoplastic samples, which is higher than in other studies.…”
Section: Dna Hypermethylation In Gatric Tissuecontrasting
confidence: 60%
“…On the other hand, the FHIT hypermethylation frequency was 61.5% in nonneoplastic samples, which is higher than in other studies. Roa et al [34] reported that FHIT was methylated in 62% of 47 GC samples. Schildhaus et al [35] Figure 2 Methylation status of CDH1, FHIT, MTAP and PLAGL1 promoter in the samples studied.…”
Section: Dna Hypermethylation In Gatric Tissuementioning
confidence: 99%
“…[37][38][39] Further studies have reported loss of Fhit not due to altered transcript but to promoter hypermethylation of the FHIT gene in breast, gallbladder and NSCL cancers. 36,[40][41][42] On the other hand, we recently showed that downregulation of Fhit protein recently showed that downregulation of Fhit protein levels in the presence of a normal mRNA can occur through Fhit protein posttranslational modification. 43 Our work began based on the observation that Fhit can be phosphorylated by Src on tyrosine 114.…”
Section: E S B I O S C I E N C E D O N O T D I S T R I B U T Ementioning
confidence: 99%
“…APC promoter methylation also occurs in a significant number of primary breast tumours (ranging from 28 to 53% of cases, depending on the applied technology) (Jin et al, 2001;Virmani et al, 2001;Liu et al, 2007). The frequency of APC methylation in primary breast tumours increases with tumour stage and size (Virmani et al, 2001;Roa et al, 2004;Chen et al, 2007;Liu et al, 2007). Moreover, hypermethylation of APC can be detected in breast aspirate fluid DNA (Lee et al, 2004) and serum DNA from patients with pre-invasive and early-stage breast cancer (Dulaimi et al, 2004a).…”
mentioning
confidence: 99%